Efeito do relaxamento muscular progressivo como intervenção de enfermagem na qualidade do sono, depressão e estresse em pessoas com esclerose múltipla - Novais, Paolla Gabrielle Nascimento (2015)
Introduction: Multiple sclerosis is a chronic, autoimmune disease, characterized by demyelination and neurodegeneration of the central nervous system. The progressive course of this disease may cause individuals to develop extreme dependency and create serious difficulties both to the individuals themselves and family members and caregivers, since the disease brings a number of physical, emotional, psychological and social symptoms. Therefore, it is essential to offer healthcare practices that go beyond the usually fragmenting, dehumanized care services that focus on the disease bodily processes. Objective: Evaluate the effects of Progressive Muscle Relaxation on sleep quality and on stress and depression levels of individuals with multiple sclerosis.